Legal nature of workers attestation - Вишновецький, Вадим Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article is devoted to the research of legal nature of attestation of state officials. In particular, in thearticle open up the generals of attestation, its features and purposes. Also considerable attention is spared tothe differences between attestation and similar legal phenomena.